2014
DOI: 10.1208/s12249-014-0238-0
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Emulsification of Nifedipine-Loaded Self-Nanoemulsifying Drug Delivery System

Abstract: ABSTRACT. Self-nanoemulsifying drug delivery system (SNEDDS) can be used to improve dissolution of poorly water-soluble drugs. The objective of this study was to prepare SNEDDS by using ternary phase diagram and investigate their spontaneous emulsifying property, dissolution of nifedipine (NDP), as well as the pharmacokinetic profile of selected SNEDDS formulation. The results showed that the composition of the SNEDDS was a great importance for the spontaneous emulsification. Based on ternary phase diagram, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Previously, an SME of PPD resulted in an increase of bioavailability by 3-fold [16]. The underlying mechanisms were attributable to the facilitation of lymphatic transport and the improvement in intestinal absorption, as documented previously [16,[26][27][28]. In the present study, both SME-1 and SME-2 could increase the bioavailability of PPT and PPD, but SME-1 resulted in significantly higher increases than SME-2.…”
Section: Formulationssupporting
confidence: 82%
“…Previously, an SME of PPD resulted in an increase of bioavailability by 3-fold [16]. The underlying mechanisms were attributable to the facilitation of lymphatic transport and the improvement in intestinal absorption, as documented previously [16,[26][27][28]. In the present study, both SME-1 and SME-2 could increase the bioavailability of PPT and PPD, but SME-1 resulted in significantly higher increases than SME-2.…”
Section: Formulationssupporting
confidence: 82%
“…Although oral administration is the best convenient route and has better patient compliance, bioavailability of nifedipine has been limited by poor solubility, photo-instability, or short plasma half-life [1]. Nifedipine is a BCS class II agent with a solubility of 5-6 µg/mL in the pH range from 4 to 13 [2], resulting in low bioavailability [3]. Improving solubility and membrane permeability could lead to enhance of oral bioavailability [4].…”
Section: -(2-mentioning
confidence: 99%
“…The results showed that ETP/PTX-loaded SMEDDS significantly enhanced the bioavailability compared with suspension formulation. In addition to P-gp and CYP3A inhibition, the other possible reasons for increased bioavailability may include: (a) SMEDDS maintained the drug in a solubilized state in the gastrointestinal tract and thus improved the oral bioavailability of poorly water-soluble drugs (Wu, Wang, et al, 2006); (b) the increased surface area of small droplets contributed to a significant increase in drug absorption (Shahnaz, Hartl, et al, 2011;Zhao, Huang, et al, 2013); and (c) droplets with a diameter size of <50 nm in SMEDDS dispersed rapidly in blood and lymph (Amri, Le Clanche, et al, 2014), and lymphatic transport can bypass the first-pass effect (Weerapo, Limmatvapira, et al, 2015). The tissue distribution results of ETP and PTX are presented in Figure 3.…”
Section: Pharmacokinetic and Tissue Distribution Studiesmentioning
confidence: 99%